Bio-synthetic hybrid materials and bionanoparticles : a biological chemical approach towards material science - Boker, Alexander; Rijn, Patrick van (Cambridge, UK : Royal Society of Chemistry, 2015)
There is much interest in using biological structures for the fabrication of new functional materials. Recent developments in the particle character and behaviour of proteins and viral particles have had a major impact on the development of novel nanoparticle systems with new functions and possibilities. Bio-Synthetic Hybrid Materials and Bionanoparticles approaches the subject by covering the basics of disciplines involved as well as recent advances in new materials. The first section of the book focusses on the design and synthesis of different bionanoparticles and hybrid structures including the use of genetic modification as well as by organic synthesis. The second section of the book looks at the self-assembling behaviour of bionanoparticles to form new materials. The final section looks at bionanoparticle-based functional systems and materials including chapters on biomedical applications and electronic systems and devices. Edited by leading scientists in bionanoparticles, the book is a collaboration between scientists with different backgrounds and perspectives which will initiate the next generation of bio-based structures, materials and devices.--
Includes bibliographical references and index.
Keywords: Nanostructured materials; Nanoparticles